Keluarga sebagai Basis Pendidikan Kristen - Armela Nababan; Agriva Pandiangan; Renaldi Setiawan; Selfius Dur; Baginda Sitompul (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
The family is the first and primary institution established by God as the foundation of Christian education. Through the family, Christian faith, moral values, and character are instilled in children from an early age. This study aims to examine the role of the family as the basis of Christian education by focusing on parents as the primary educators, Christian family spirituality, faith education for children and adolescents, challenges faced by modern families, and the application of Christian parenting. The research employs a qualitative method using a library research approach by collecting and analyzing various literature sources relevant to the topic. The findings indicate that the success of Christian education within the family is greatly influenced by the active involvement of both fathers and mothers in guiding the spiritual lives of their children. Fathers serve as spiritual leaders and role models within the family, while mothers function as educators and caregivers who instill Christian values in daily life. Children also have the responsibility to honor their parents and grow in faith toward God. Furthermore, family spirituality expressed through family prayer, Bible reading, and family worship serves as an essential foundation for the spiritual growth of family members. Amid the rapid development of technology, social media, and secular culture, Christian families face various challenges that require parenting practices grounded in biblical principles. Therefore, Christ-centered families can effectively nurture a generation with strong faith, good character, and the ability to become witnesses of Christ in society.